Internalization of Islamic Values for Students with Special Needs in Special School Education Institutions (SLB) - Arif Wahyudi; Miftachul Huda (Al-Hayat Al-Istiqomah Foundation, 2019)
This research is based on the assumption that the need to internalize Islamic religious education is more effective in knowing how much students absorb in learning Islamic religious education. Internalization of Islamic education can be used as a reference as a better learning process. The purpose of this study was to describe the concepts, constraints and solutions to the internalization of Islamic religious education for children with special needs at the Extraordinary Middle School Kemala Bhayangkari, Trenggalek, East Java, Indonesia. The research method uses a qualitative approach. Data collection is done using observation, interview and documentation techniques. Check the validity of the data with confirmation techniques and peer discussions. Data analysis using interactive analysis, namely conceptualization, categorization, then reduced, the presentation of the data then held conclusions. The results of the study: 1) The concept of internalization starts from learning planning tailored to the conditions of students so that they can receive the planting of religious values ​​well. 2) Constraints on internalizing Islamic values ​​for students with special needs, namely the difficulty of the teacher in determining indicators of student success in absorbing the material that has been taught, lack of teacher knowledge about the nature of students with special needs (in this case mental retardation) and the psychology of child development in general, not yet available and supporting infrastructure to the fullest. 3) Solution to the internalization of Islamic values ​​for children with special needs: Islamic religious education teachers to always improve the quality of learning and teaching experience consciously and independently through the MGMP forum and also with efforts by the leadership of institutions that always encourage teachers to improve quality of teacher resources by including in trainings or seminars, workshops, FGD (forum group discussions), etc. relating to children with special needs (mental retardation). Penelitian ini didasarkan pada anggapan perlunya internalisasi pendidikan agama Islam yang lebih efektif untuk mengetahui seberapa besar penyerapan siswa dalam pembelajaran pendidikan agama Islam. Internalisasi Pendidikan agama Islam dapat dijadikan acuan sebagai proses pembelajaran yang lebih baik lagi. Tujuan penelitian ini adalah mendeskripsikan konsep, kendala dan solusi internalisasi pendidikan agama Islam anak berkebutuhan khusus di Sekolah Menengah Pertama Luar Biasa Kemala Bhayangkari, Trenggalek, Jawa Timur, Indonesia. Metode penelitian menggunakan pendekatan kualitatif. Pengumpulan data dilakukan dengan menggunakan teknik observasi, wawancara dan dokumentasi. Pemeriksaan keabsahan data dengan teknik konfirmasi dan diskusi teman sejawat. Analisis data menggunakan analisis interaktif yaitu konseptualisasi, kategorisasi, kemudian direduksi, penyajian data selanjutnya diadakan penarikan kesimpulan. Hasil penelitian: 1) Konsep internalisasi dimulai dari perencanaan pembelajaran disesuaikan dengan kondisi siswa agar mereka dapat menerima dengan baik penanaman nilai religius. 2) Kendala internalisasi nilai Islami bagi siswa berkebutuhan khusus yaitu kesulitan guru dalam menentukan indikator keberhasilan siswa dalam menyerap materi yang telah diajarkan, minimnya pengetahuan guru tentang hakekat siswa berkebutuhan khusus (dalam hal ini tunagrahita) dan tentang psikologi perkembangan anak secara umum, belum tersedia sarana dan prasarana pendukung secara maksimal. 3) Solusi internalisasi nilai Islami bagi anak berkebutuhan khusus: guru pendidikan agama Islam agar selalu meningkatkan kualitas belajar dan pengalaman mengajar secara sadar dan mandiri melalui forum Musyawarah Guru Mata Pelajaran (MGMP) dan juga dengan upaya oleh pimpinan lembaga yang selalu mendorong para guru untuk meningkatkan kualitas sumber daya guru dengan mengikut sertakan dalam pelatihan-pelatihan atau seminar, workshop, FGD (forum group discussion), dll yang berkaitan dengan anak berkebutuhan khusus (tunagrahita).